Curvature-Induced Changes in the Magnetic Energy of Vortices and Skyrmions in Paraboloidal Nanoparticles - Altbir-Drullinsky, D; Elias-Moreno, R; Carvalho-Santos, V (American Institute of Physics, 2015)
Curvature effects are important for a proper description of the properties of magnetic systems. In this paper, the exchange and dipolar energy of vortices on a paraboloidal shell is studied. Using analytical calculations, it is shown that the in-plane component of vortices has larger energy on a paraboloidal shell than in a planar disk with same thickness. On the other hand, the dipolar energy associated to the vortex core diminishes if the vortex core is on a paraboloidal surface. This reduction in the dipolar energy may cause a vortex pinning mechanism by a paraboloidal shaped defect in a planar nanomagnet. Regarding skyrmions, by using an in-plane anisotropy approximation to the dipolar energy, it is shown that the skyrmion must have its width shrunk in order to diminish the magnetostatic energy and satisfy geometrical constraints of the system. © 2015 AIP Publishing LLC.